Improper Pronunciation of the Vowel /ə/ in Trisyllabic Words by Kurdish EFL Learners - Aras Abdalkarim Amin (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
Identifying the pronunciation of the vowel schwa /ə/ within English words, in particular trisyllabic words, seems entirely confusing and difficult because of the fact that there are no explicit phonetic or phonological manifestations which determine where to exactly pronounce this vowel. Consequently, identifying where to pronounce /ə/ within trisyllabic words has been an issue of confusion and overlapping to learners, and, in particular, Kurdish EFL learners. The current paper investigates the improper pronunciation of /ə/ in such words by 30 university learners majoring English as a foreign language. Those learners are instructed to read a list of words which contain 30 trisyllabic words containing the vowel /ə/ in different syllables and are also instructed to transcribe each. The study explicitly demonstrates that Kurdish learners improperly and, to a certain extent, excessively replace this vowel with other vowels whether simple or diphthongs. The improper replacement is mainly the result of specific phonological attributes including the improper estimation of the qualities of the vowels within the syllables of the trisyllabic words and the improper reliance on the spelling and other related attributes.